MOTION Scenario Book - Henriksson, Kristina; Mantere, Päivi; Riihihuhta, Jami; Hardiman, Marco; Bretschneider, Jan; Topal, Kalender; Labanauskaite, Daiva; Spiriajevas, Eduardas; Ignasiak-Szulc, Aranka; Makowska, Ewa; Józefowicz, Barbara; Castañeda García, José Alberto; et al. (Laurea-ammattikorkeakoulu, 2023)
Given that tourism has been fluctuating tremendously during the past four years, the project MOTION has during that time been working on the issues of overtourism and ways on how to solve them, by finding new sustainable solutions for the future. The MOTION Scenario Book illustrates alternative futures through ideas generated in scenarios in five European regions, Rovaniemi in Finland, Fehmarn and Kiel in Germany, the Curonian Spit in Lithuania, Toruń in Poland, and Granada and Monachil in Spain. The book is intended to serve as an inspiration to those who wish to grow sustainable solutions in tourism and combat overtourism. The project was funded by the Finnish National Agency of the EU for the years 2020–2023.